2019
DOI: 10.29328/journal.jsctt.1001016
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells conditioned media promotes the wound healing process - An in vitro study

Abstract: stem cells conditioned media promotes the wound healing process-An in vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For instance, conditioned media (CM) promoted proliferation and migration of alveolar epithelial cells facilitating in vitro wound closure. [18][19][20][21] SFCM displayed beneficial effects in a Balb/C mouse model of excisional wound injury via increased deposition of regulatory macrophages and endothelial progenitor cells at the site of injury. 22 Additionally, there was improved functional recovery following hindlimb injury, induced by femoral artery ligation, via increased collateral angiogenesis and limb remodelling.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, conditioned media (CM) promoted proliferation and migration of alveolar epithelial cells facilitating in vitro wound closure. [18][19][20][21] SFCM displayed beneficial effects in a Balb/C mouse model of excisional wound injury via increased deposition of regulatory macrophages and endothelial progenitor cells at the site of injury. 22 Additionally, there was improved functional recovery following hindlimb injury, induced by femoral artery ligation, via increased collateral angiogenesis and limb remodelling.…”
Section: Introductionmentioning
confidence: 98%
“…Exosome potency assays include inhibiting T cell proliferation, macrophage phagocytosis, fibroblast activity, vascular-like network formation assay on Matrigel [167] and scratch wound healing assays [168] that are very useful and can be optimized quickly in the lab. Emerging in vivo potency assays such as EV-mediated wound healing [166,169] (assess the biological response of exosomes in a disease model [170]. Critically understanding the mechanism of how exosomes elicit a response will assist in regulatory approval.…”
Section: Technical Challengesmentioning
confidence: 99%
“…that are responsible for cell proliferation, fibroblast migration, and angiogenesis essential for wound healing. 14,15 Commonly used methods for delivery of MSC-secretome are systemic and topical administration via injections but challenges with these techniques involve rapid clearance into the circulatory system, short half-life, degradation by macrophages or local tissue environment, and cost of repeated injections are relatively high due to high cost of production and purification. 16 Antunes et al demonstrated that multiple small doses of small EVs had higher wound healing as compared with single high dose of EVs as wound healing is complex multiple day process, which can be achieved using hydrogels by tuning its physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Jain et al using our proprietary technology has demonstrated the biocompatibility of MSC‐secretome as well as presence of 105 cytokines and growth factors in the MSC‐secretome like VEGF, FGF, collagen, etc. that are responsible for cell proliferation, fibroblast migration, and angiogenesis essential for wound healing 14,15 16 .…”
Section: Introductionmentioning
confidence: 99%